2009
DOI: 10.5004/dwt.2009.623
|View full text |Cite
|
Sign up to set email alerts
|

Properties of amino-functionalized silica membranes for the dehydration of water/ethanol mixtures

Abstract: ab s t r ac tAmino-functionalized silica membranes were applied to the separation of water/ethanol mixtures by pervaporation. An increased interaction between the silica membrane surface and permeating materials is important in order to enhance separation. In this study, the improvement in water permeance ability and selectivity was examined by modifying the silica membrane surface with amino groups. Silica membranes were prepared by the sol-gel method of hydrolysis and cocondensation processes using tetraetho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These peaks are clearly observed in the specta of AF-MSM and are due to aminopropyl groups. Additionally, the presence of aminopropyl groups in AF-MSM was confirmed by a broad band extending from 2800 to 3400 cm -1 corresponding to the stretching vibration of NH þ 3 and also by a peak at 1510 cm -1 due to the symmetric bending vibration of -NH 2 [49][50][51][52]. These peaks increased with increasing APTES content, thus the introduction of amino groups increased with increasing APTES in AF-MSM.…”
Section: Characterization Of Aminopropyl-functionalized Silica Microsmentioning
confidence: 84%
“…These peaks are clearly observed in the specta of AF-MSM and are due to aminopropyl groups. Additionally, the presence of aminopropyl groups in AF-MSM was confirmed by a broad band extending from 2800 to 3400 cm -1 corresponding to the stretching vibration of NH þ 3 and also by a peak at 1510 cm -1 due to the symmetric bending vibration of -NH 2 [49][50][51][52]. These peaks increased with increasing APTES content, thus the introduction of amino groups increased with increasing APTES in AF-MSM.…”
Section: Characterization Of Aminopropyl-functionalized Silica Microsmentioning
confidence: 84%
“…. Therefore, 3-aminopropyltriethoxysilyl (APTES) as an amine source, which exhibits strong CO 2 affinity, has been utilized extensively to functionalize silica because the defect-free surface was found difficult to obtain with pure APTES owing to the faster condensation rate of amine–organic–silane . Currently, this desired structure with the appropriate APTES content has been achieved via postsynthesis and co-condensation methods. Co-condensation is an attractive one-step sol–gel strategy involving the functionalization of silica with the carefully controlled incorporation of CO 2 -philic groups to achieve the desired microporous structure .…”
Section: Introductionmentioning
confidence: 99%
“…The potential of these membranes in separation applications has led to increasing interest into the synthesis of inorganic membranes based on ordered mesoporous silicas. Mesoporous siliceous membranes are generally prepared on porous substrates by templating silicates with surfactant micelles and using dip-coating or spin-coating techniques, or hydrothermal treatment. For a full review of the synthesis of mesoporous silica membranes, we refer the reader to the review article of van de Water and Maschmeyer and the recent paper of Chew et al A number of studies have reported the use of these membranes, either pure or functionalized, for separations including ethanol/water, He/N 2 , CO 2 /N 2 , ,, He/CH 4 , He/N 2 , He/Ar, He/C 3 H 8 , He/CO 2 , and CO 2 /C 3 H 8 …”
Section: Introductionmentioning
confidence: 99%